Visualizing Empire : Africa, Europe, and the Politics of Representation - Thomas, Dominic Richard David; Nelson, Steven, 1962-; Peabody, Rebecca; Terpak, Frances, 1948- (Book collections on Project MUSE., 2021)
"The essays in this book analyze aspects of colonialism through investigations into the art, popular literature, material culture, film, and exhibitions that represented, celebrated, or were created for France's colonies across the seas. These studies draw from documents and media-photographs, albums, postcards, maps, posters, advertisements, and children's games-related to the nineteenth- and twentieth-century French Empire"--